Comparison of the Efficacy of Atorvastatin and Rosuvastatin in Preventing Atrial Fibrillation after Coronary Artery Bypass Grafting: A Double-blind Randomized Comparative Trial - Zahra Samadifar; Naser Aslanabadi; Babak Kazemi Arbat; Ahmad Separham; Elnaz Javanshir (Journal of Tehran University Heart Center, 2023)
Background: Atrial fibrillation (AF) is a supraventricular tachyarrhythmia characterized by disorganized atrial activity and subsequent mechanical atrial failure. Postoperative AF is a frequent complication of coronary artery bypass grafting (CABG). Although there is evidence of decreased AF after CABG with statin usage, information is scarce regarding a direct comparison between atorvastatin and rosuvastatin. The present study was conducted to compare the efficacy of rosuvastatin and atorvastatin in preventing post-CABG AF.